2023
DOI: 10.1111/1753-0407.13373
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the retinal neurovascular unit: New perspectives into diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is one of the most prevalent retinal disorders worldwide, and it is a major cause of vision impairment in individuals of productive age. Research has demonstrated the significance of autophagy in DR, which is a critical intracellular homeostasis mechanism required for the destruction and recovery of cytoplasmic components. Autophagy maintains the physiological function of senescent and impaired organelles under stress situations, thereby regulating cell fate via various signals. As th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…S2C ). Autophagy malfunction is known to be critically involved in the pathogenesis of DR, including the damage of the NVU ( Yang et al, 2023 ). Surprisingly, we did not detect any significant changes in autophagy-related genes in Müller cells.…”
Section: Resultsmentioning
confidence: 99%
“…S2C ). Autophagy malfunction is known to be critically involved in the pathogenesis of DR, including the damage of the NVU ( Yang et al, 2023 ). Surprisingly, we did not detect any significant changes in autophagy-related genes in Müller cells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to surgery alone or anti-VEGF therapy, herbal monomers for the treatment of DR have received extensive attention from academic researchers recently because of their mild side effects. [116,117] Overall, autophagy has clearly become a research hotspot for DR. [27,116] The majority of evidence indicates that autophagy plays a dual role in time and volume accumulation (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, autophagy has clearly become a research hotspot for DR. [ 27 , 116 ] The majority of evidence indicates that autophagy plays a dual role in time and volume accumulation (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 For example, in the physiological state or at the early stage of some diseases, autophagy helps to clear senescent and damaged cells or organelles, while when autophagy is too strong, it has a pathogenic effect on cells, tissues, and organs. 10 Recently, many researches demonstrated that activating autophagy might be a promising therapeutic strategy in DR. 11 , 12 Adenosine monophosphate-activated protein kinase (AMPK) participates in the regulation of energy metabolism, plays a protective role in many diseases including DR. 13 Sirtuin 1 (SIRT1), one of the sirtuins family members, is a nicotinamide adenine dinucleotide (NAD +)-dependent histone deacetylase. SIRT1 is activated by the increase of intracellular adenosine monophosphate and NAD + levels.…”
Section: Introductionmentioning
confidence: 99%